The effectiveness of android applications that integrate deep learning approaches for early childhood sexual education - Dessy Farantika; Devi Candra Nindiya; Firda Roudlotul Hidayah; Maulinda Sanjaya Sulistiyani (Psychology, Evaluation, and Technology in Educational Research, 2026)
Sexual education is a fundamental understanding for children about sex from the moment they begin to interact with others and to protect themselves preventively. The selection of an Android application, considering its user-friendly, flexible, and efficient operating system, along with the inclusion of sexual education games, can enhance children's sexual education knowledge in an enjoyable manner. This study aims to determine the effectiveness of an Android-based application integrating a deep learning approach as sexual education for children aged 4-6 years. The research method and model development used the ADDIE model. The research subjects were students aged 4-6 years, teachers, and parents/guardians at two kindergartens in Blitar City, Indonesia. Data collection techniques included observation, interviews, and questionnaires. Data analysis techniques included formative evaluation to examine the validity of the application at each stage of the ADDIE model and summative evaluation to assess the effectiveness of the application in improving sex education. The findings show that the Android-based sexual education application that integrates the deep learning approach for children aged 4-6 years is feasible and proven to be effective, efficient, and interesting. Through the integration of the deep learning approach in the developed sexual education application, it can create meaningful, self-aware, and enjoyable learning for students. The sexual education application shows great promise in enriching early childhood education by integrating the deep learning approach and utilizing.